Novel Antihypertension Mechanism of β-Glucan by Corin and ANP-Mediated Natriuresis in Mice - Sun Jung Lee; Dong Hee Lee; Ha Won Kim (Mycobiology, 2020)
Many of the β-glucans are known to have antihypertensive activities, but, except for angiotensin-converting enzyme II inhibition, the underlying mechanisms remain unclear. Corin is an atrial natriuretic peptide (ANP)-converting enzyme. Activated corin cleaves pro-ANP to ANP, which regulates water–sodium balance and lowers blood pressure. Here, we reported a novel antihypertensive mechanism of β-glucans, involved with corin and ANP in mice. We showed that multiple oral administrations of β-glucan induced the expression of corin and ANP, and also increased natriuresis in mice. Microarray analysis showed that corin gene expression was only upregulated in mice liver by multiple, not single, oral administrations of the β-glucan fraction of Phellinus baumii (BGF). Corin was induced in liver and kidney tissues by the β-glucans from zymosan and barley, as well as by BGF. In addition to P. baumii, β-glucans from two other mushrooms, Phellinus linteus and Ganoderma lucidum, also induced corin mRNA expression in mouse liver. ELISA immunoassays showed that ANP production was increased in liver tissue by all the β-glucans tested, but not in the heart and kidney. Urinary sodium excretion was significantly increased by treatment with β-glucans in the order of BGF, zymosan, and barley, both in 1% normal and 10% high-sodium diets. In conclusion, we found that the oral administration of β-glucans could induce corin expression, ANP production, and sodium excretion in mice. Our findings will be helpful for investigations of β-glucans in corin and ANP-related fields, including blood pressure, salt–water balance, and circulation.